Analysis of Fabrication Material Inventory Control Strategy Using AHP, MUSIC-3D and MIN-MAX STOCK approaches at PT. Bangun Teknik - Purba, Arini Anestesia; Rohmatin, Yuli Nuri; Karim, Abdul Aliul (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2024)
PT Bangun Teknik Baja is a manufacturing company engaged in Fabrication, Repairing, and Machining for heavy mining equipment. The company does not yet have a basic strategy in carrying out inventory planning actions, so the amount of material ordered is only based on the estimated number of production product needs. Therefore, excessive amounts of inventory (overstock), lack of inventory (out of Stock) and frequent occurrence of Deadstock often occur. Order data, usage data and stock data on 50 types of fabrication materials with an average of 25 materials experiencing overstock, 4 materials out of stock and there are 221 Deadstock materials from August 2021 to July 2023 are used as the basis of this research. To determine the most suitable inventory control strategy according to the needs of PT Bangun Teknik Baja, processing is carried out with AHP, Music-3D with ABC, FSN and SDE Classification, and Min-Max Stock. AHP produces the most important priority classification dimension criteria, namely ABC, FSN and SDE with the most important sub-criteria being A,B,C,F,S,N,D,E,S. These results are used as a reference for Music-3D processing which produces 9 groups of material categories according to their respective characteristics of importance, namely AFD, AFE, ASE, BFE, BSE, CFD, CFE, CSD, and CSE, the 9 categories obtained their respective policy solutions by applying Min-Max Stock, by obtaining minimum and maximum limits on each material to minimize waste. ROP and Safety Stock calculations are used to minimize Overstock in minimizing Deadstock and Out Of Stock to minimize losses, so it is proven that the application of Min-Max Stock can save Total Inventory Cost by 1.45% from the company's actual policy.